2000
DOI: 10.1023/a:1005136531079
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond the Illness: Factors Contributing to Gaining and Maintaining Employment

Abstract: The work presented here, exploratory in nature, uses a comparative and qualitative approach to understand the factors associated with the ability of individuals with severe and persistent mental illness to successfully gain and maintain employment. Based on open-ended interviews with individuals in an Assertive Community Treatment (ACT) program, we compare the experiences of those who have been successful gaining and maintaining employment, with those who have been successful gaining but not maintaining work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 22 publications
5
27
0
Order By: Relevance
“…Our subsequent analyses revealed that at least two factors independently put some MAP students at especially high risk of unemployment: having a serious mental illness at the beginning of MAP; and having relatively small improvements in work skills. These findings are consistent with past work on poor mental health as a barrier to competitive employment, potentially due to stigma and discrimination as well as poor coping skills, communication problems, and other functional limitations (Cunningham, Wolbert, & Brockmeier, 2000; Taskila et al, 2014). Perhaps the MAP environment is not well suited to help students with serious mental illness secure future competitive employment once they leave its supportive environment.…”
Section: Discussionsupporting
confidence: 89%
“…Our subsequent analyses revealed that at least two factors independently put some MAP students at especially high risk of unemployment: having a serious mental illness at the beginning of MAP; and having relatively small improvements in work skills. These findings are consistent with past work on poor mental health as a barrier to competitive employment, potentially due to stigma and discrimination as well as poor coping skills, communication problems, and other functional limitations (Cunningham, Wolbert, & Brockmeier, 2000; Taskila et al, 2014). Perhaps the MAP environment is not well suited to help students with serious mental illness secure future competitive employment once they leave its supportive environment.…”
Section: Discussionsupporting
confidence: 89%
“…While this study does not necessarily support a relationship between coping and competitive employment, it indicates that coping impacts skills related to employment success. In addition, two qualitative studies (Cunningham, Wolbert, & Brockmeir, 2000; Becker, Whitley, Bailey, & Drake, 2007) examined the variables perceived as being related to job success among persons with severe mental illness who had found and maintained employment. In both studies, participants highlighted the importance of using effective coping skills to deal with work-related stress.…”
Section: Review Of Evidence For the Modelmentioning
confidence: 99%
“…In both studies, participants highlighted the importance of using effective coping skills to deal with work-related stress. Of note, Cunningham et al (2000) compared groups of mental health consumers who had and had not been successful in finding gainful employment, and found differences in the way employed and unemployed consumers talked about coping, with employed consumers discussing more problem-oriented coping.…”
Section: Review Of Evidence For the Modelmentioning
confidence: 99%
“…The model stipulates that functioning, in our terms work-ability, encompasses mutually related components: disease and disorder, functions and structures, activities, participation, and personal and environmental factors. In recent systematic reviews on factors influencing work participation of young disabled people [14][15][16] several determinants from different components of the ICF model were found to influence work outcome. As health related factors severity of condition, co-morbidity, chronic health conditions combined with mental retardation and inpatient treatment were found.…”
Section: Introductionmentioning
confidence: 99%